Role of Personality Traits in Psychological Treatment - Le Corff, Yann (Canadian Journal of Counselling and Psychotherapy, 2011)
Based on a literature review, this article discusses the role of personality traits in psychological treatment. First, personality traits theory and the Five-Factor Model of Personality are introduced. The main body of the article discusses the influence of personality traits on the choice of therapeutic approach, therapeutic alliance, counter-transference, treatment compliance, and the choice of therapeutic goals in light of the temporal stability of traits. In conclusion, suggestions are made for future research so that clinicians can benefit from the full potential of evaluating their clients’ personality traits.